Diagnostic and therapeutic management of subclinical endometritis in dairy bovine: A Review - Parikh, S.S.; Kavani, F.S.; Parmar, K.H.; Patbandha, T.K.; Singh, V.K.; Ahlawat, A.R.; Kumar, Rajesh (Animal Reproduction Update, 2022)
Subclinical endometritis (SCE) is one of the major causes of repeat breeding syndrome in dairy bovines, characterized by the presence of polymorpho nuclear (PMN) cells within uterine cytology sample during early postpartum period. In dairy bovines, on an average 20-53 % animals suffer from SCE between 20 and 60 days post-calving due to variable risk factors. Among various diagnostic techniques, cytotape method of sample collection is comparatively superior to cytobrush and other techniques for early diagnosis of SCE in dairy bovine. A variable result of conventional therapy for successful management of uterine infections justifies the interest in stimulation of uterine defence mechanism to combat uterine infections. Natural resources particularly phyto-medicines can help to overcome the losses due to SCE in dairy bovines. Proper understanding of risk factors for SCE and its early identification followed by timely therapeutic interventions can minimize the losses incurred by the farmers in dairy bovines owing to SCE.
Keywords: Dairy bovine; Diagnosis; Subclinical endometritis; Therapeutic management